2023
DOI: 10.1177/08927057231180479
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of nanocellulose fiber (CNF) by biological enzymatic method

Abstract: In this paper, using Styphnolobium japonicum, Cryptomeria fortunei and Pinus yunnanensis as raw materials, cellulose (CE) was first extracted by chemical method (CM1) and biological enzymatic method 2 (BM2), and then further prepared into nanocellulose fiber (CNF) by biological enzymatic method 1(CPM (CPM stands for cellulase and pectinase)). The CE and CNF were characterized by FTIR, XRD, SEM, DSC and TG. The results showed that the CNF prepared by CM1-CPM was cellulose type II, CNF prepared by BM2-CPM was ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…In cellulose, every single monomer unit comprises three hydroxyl groups responsible for cellulose's bonding and characteristic properties. Different types of methods have been reported to isolate the Cellulose Nano Fiber (CNF) from lignocellulosic materials, which include acid hydrolysis (yellow thatching grass) [3], high-pressure homogenization, ball milling, and grinding [4], catalytic oxidation (e.g., Oryza sativa) [5], ultrasonication [1] and enzymatic technique [6], respectively. Chemo-mechanical treatment increases the interfacial bonding strength by making the CNF surface available for further modification through hydrogen bonding during the preparation of CNF-based nanocomposites and potential mechanical interlocking between the CNF surface and base matrix of polymer nanocomposite [7].…”
Section: Introductionmentioning
confidence: 99%
“…In cellulose, every single monomer unit comprises three hydroxyl groups responsible for cellulose's bonding and characteristic properties. Different types of methods have been reported to isolate the Cellulose Nano Fiber (CNF) from lignocellulosic materials, which include acid hydrolysis (yellow thatching grass) [3], high-pressure homogenization, ball milling, and grinding [4], catalytic oxidation (e.g., Oryza sativa) [5], ultrasonication [1] and enzymatic technique [6], respectively. Chemo-mechanical treatment increases the interfacial bonding strength by making the CNF surface available for further modification through hydrogen bonding during the preparation of CNF-based nanocomposites and potential mechanical interlocking between the CNF surface and base matrix of polymer nanocomposite [7].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 It was reported that the extraction of cellulose from various plants, namely Styphnolobium japonicum, Cryptomeria fortunei and Pinus yunnanensis, could be attained by using the chemical method and biological enzyme, then further prepared into nano cellulose fibers. 5 Besides, nanoscale cellulose also possesses a high aspect ratio, surface area, strength, and modulus. [6][7][8] The high performance and exceptional mechanical features of nanocellulose make it a remarkable candidate for developing sustainable composite materials to meet the future demands of modern technology in a wide range of applications.…”
Section: Introductionmentioning
confidence: 99%